The week-of-the-year effect: Evidence from around the globe - Levy, Tamir; Yagil, Joseph (Journal of Banking & Finance, 2012)
This study investigates another calendar anomaly the literature does not yet address – the week-of-the-year (WOY) effect. Using the weekly returns on the stock market indexes of 20 countries worldwide, for a period that ends in December 2010, the findings demonstrate that returns in Week 44, which starts on October 29 and ends on November 4, are positive in 19 of the 20 countries, and in 18 of them, it is also statistically significant. In contrast, the returns for Week 43, which starts on October 22 and ends on October 28, are negative in 19 of the 20 countries, and statistically significant for most of the countries. We also apply an investment strategy derived from these findings to a prediction period (2009–2010), and find that this strategy beats the simple buy-and-hold policy by a substantial margin.